Materials for conservation : organic consolidants, adhesives, and coatings - Horie, C. V. (Charles Velson) (Butterworths series in conservation and museology., 1987)
Materials for Conservation: Organic Consolidants, Adhesives and Coatings provides an overview of one aspect of materials conservation treatment, particularly the properties of organic consolidants, adhesives, and coatings. The contents of the book are divided into two parts; these parts are background information and survey of polymers. The coverage of the first part includes polymer science and the uses and requirements of applied polymers. The second part covers resins, vinyl, thermoplastics, fillers, and colorants. The text will be most useful to individuals involved in the management and c.